Exploring a model of servant leadership, empowerment, and commitment in nonprofit organizations. Issue 1 (14th March 2018) - Allen, Stuart; Winston, Bruce E.; Tatone, Gia R.; Crowson, Howard M.
Abstract : This study examined a model of servant leadership's relationship to organizational commitment through structural and psychological empowerment, focusing on leader–follower dyads in a nonprofit organization. Survey data was collected from 128 employees of a nonprofit organization in a northeastern U.S. city. After model re‐specification, a well‐fitting model emerged, indicating that structural empowerment mediates the relationship between servant leadership and organizational commitment. Moreover, the model suggests that structural empowerment's effect on organizational commitment is both direct and indirect—the latter occurring through the meaning dimension of psychological empowerment. This study provides initial support for structural empowerment being a mechanism through which servant leadership impacts organizational commitment in nonprofits. In addition, the role of meaningful work is highlighted as an antecedent to organizational commitment for nonprofit employees. Servant leaders are suggested to create structurally empowering working environments, which support employees' stronger commitment to the organization.